2011
DOI: 10.5398/medpet.2011.34.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Growth and Distribution in Fattening Steer of Different Breeds

Abstract: The breed pa erns in growth and distribution of muscle were studied using three breeds of beef ca le entering fa ening phase. This study involved 23 grass-fed steer Brahman, 24 Hereford and 22 Brahman x Hereford crosses with a live weight range of 300 to 600 kgs. An allometric Huxley model was used to study the growth and distribution pa erns of muscle tissue within wholesale cut. There were several cuts in which the muscle growth coeffi cients were signifi cantly diff erent among breeds. Comparisons of muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Unlike the growth of muscle within wholesale cuts (Priyanto & Johnson, 2011), the growth of fat showed more widespread breed variations, 11 of the 15 wholesale cuts differing significantly among breed groups (Table 1). In most cases, Brahmans had significantly higher growth coefficients than Herefords and/or BrahmanxHereford crosses while Herefords and BrahmanxHereford crosses had similar growth coefficients in wholesale cuts.…”
Section: Results and D�scuss�onmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the growth of muscle within wholesale cuts (Priyanto & Johnson, 2011), the growth of fat showed more widespread breed variations, 11 of the 15 wholesale cuts differing significantly among breed groups (Table 1). In most cases, Brahmans had significantly higher growth coefficients than Herefords and/or BrahmanxHereford crosses while Herefords and BrahmanxHereford crosses had similar growth coefficients in wholesale cuts.…”
Section: Results and D�scuss�onmentioning
confidence: 99%
“…Whilst such studies could provide useful information about patterns of fat growth and distribution, the genetic variation in fattening patterns could not be clearly identified by this approach. Priyanto & Johnson (2011) reported breed variation in muscle weight distribution whitin wholesale cuts when adjusted to the same carcass weight. The present study confirmed the previous findings that there were significant between breed differences in the growth and distribution of carcass fat whitin wholesale cuts relative to fat-free carcass weight.…”
Section: Results and D�scuss�onmentioning
confidence: 99%
See 1 more Smart Citation